Comparison of 18F-fluoride positron emission tomography and magnetic resonance imaging in evaluating early-stage osteoarthritis of the hip. Issue 1 (January 2015) - Kobayashi, Naomi; Inaba, Yutaka; Tateishi, Ukihide; Ike, Hiroyuki; Kubota, So; Inoue, Tomio; Saito, Tomoyuki
Abstract : Objective: The imaging diagnosis of osteoarthritis (OA) of the hip, especially in its early stages, is a technically challenging but essential aspect of our increased understanding of the pathophysiology of this disorder. We recently applied 18 F-fluoride PET for the detection of abnormal bone turnover in early-stage OA. In our current study, we have compared the diagnostic and analytical capabilities of 18 F-fluoride PET and MRI modalities in a hip OA patient series. Patients and methods: A total of 85 hip joints, including hips at various stages of OA as well as painful, dysplastic, and normal contralateral hips, were analyzed. The average age of our study patients was 50 (range 24–75) years. The Kellgren and Lawrence (K/L) grade was used for radiographic evaluations. Hip pain was graded on the basis of pain severity. 18 F-Fluoride PET and MRI data obtained during the same period (within 3 months) were compared for all joints in the study. Results: We identified PET positivity (i.e. SUVmax >6.5) in 47 joints, whereas MRI-positive findings were evident in 25 joints. Most (96%) of the MRI-positive joints were also PET positive. The percentage of MRI-positive joints and PET uptake-positive joints was 6 and 18% in K/L grade 0, 16 and 48% in K/L grade 1, 27 and 65% in K/L grade 2, 73 and 87% in K/L grade 3, and 100 and 100% in K/L grade 4, respectively. Among the 23 MRI-negative but PET-positive joints, 21 joints had a K/L grade below 2, and 12 joints showed greater than moderate hip pain. Conclusion: 18 F-Fluoride PET can detect bone abnormalities earlier than MRI in OA of the hip. This probably reflects accelerated bone remodeling due to high stress and may be followed by the appearance of bone marrow edema on MRI.